Junie B. Jones and a little monkey business : the graphic novel - Park, Barbara; Park, Barbara; Venable, Colleen A. F. (Junie B. Jones graphic novels, 2025)
Through a misunderstanding, Junie B. thinks that her new baby brother is really a baby monkey, and her report of this news creates excitement and trouble in her kindergarten class.